PENGARUH PELATIHAN SAFETY BEHAVIOR TEHADAP PENGETAHUAN DAN SIKAP KELOMPOK USAHA KECIL MENENGAH (UKM) DI SEKITAR UNSOED PURWOKERTO - Suryanto, Suryanto; Heryanto, Heryanto; Andodo, Candra (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2015)
ABSTRACTApproximately 85% of the incidence of occupational accidents due to human factors (human error) that behave in unsafe work. Wrong behavior (unsafe) can be improved by increasing the knowledge and attitudes through training in group of tmerchants. The purpose of the study to knowing the effect of safety behavior training on knowledge and attitude of the group small and medium merchants around Unsoed Purwokerto. This study uses a quasi-experimental design with one group pretest and posttest design. Data analysis was performed using paired t-test or Wilcoxon test. Population of 120 merchants and samples were taken by purposive sampling with a sample size of 40 people. The results showed no differences in the respondents' knowledge after training at posttest I and posttest II with p = 0.028 (<0.05) and no difference between the attitudes of respondents to the pretest posttest II with p = 0.036 (<0.05). Conclusions of this researchThe training program can increase knowledge and change the attitudes of respondents significantly. Suggest for team of lecturers to be able to follow up this study with further research and community service activities as traders SMEs still need guidance and advocacy in the workplace in increasing labor productivity.Keywords: Training, Safety behavior, knowledge, attitudes, work accidents. Kesmasindo, Volume 7, (2) Januari 2015, Hal. 132-144